Design And Implementation On Prototype Of Web Based Home Monitoring And Lamps Controlling Based On Arduino System - ZAKARIA, Iham Nur, Dr. Ir. Bana Handaga, MT, Dedy Ary Prasetya ST (2015)
Smart Home is a technology that makes the house be smart and automatic. Typically, these technologies have automated systems for lighting, control, security and many other functions. Smart Home System is designed and made by utilizing WLAN network based on the Arduino microcontroller. Ethernet shield is able to connectArduino to the network via TCP / IP communication. This system is capable of home monitoring and lamps controlling. There are three sensors used to monitor home includes two PIR and a LM35 temperature sensor. PIR sensors are used to detect of motion. A LM35 temperature sensor is used to monitor temperature in room. The home monitoring and lamps controlling are displayed on a web page by laptop and smartphone. Key words :Arduino Uno, WLAN, Ethernet Shield, PIR sensors, LM35 temperature sensor